Agent based modelling of urban systems : first International Workshop, ABMUS 2016, held in conjunction with AAMAS, Singapore, Singapore, May 10, 2016, Revised, selected, and invited papers /: first International Workshop, ABMUS 2016, held in conjunction with AAMAS, Singapore, Singapore, May 10, 2016, Revised, selected, and invited papers. (2017) - Unknown
No abstract available